2014
DOI: 10.4055/cios.2014.6.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Salient Features of the Maasai Foot: Analysis of 1,096 Maasai Subjects

Abstract: BackgroundThe Maasai are the most widely known African ethnic group located in Kenya and northern Tanzania. Most spend their days either barefoot or in their traditional shoes made of car tires. Although they walk long distances of up to sixty kilometers a day, they do not suffer from any foot ailments. Little is known about their foot structure and gait. The goal of this investigation was to characterize various aspects of Maasai foot in standing and walking.MethodsFoot length, calf circumference, hindfoot al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
1
3
0
1
Order By: Relevance
“…Interestingly, the prevalence of claw toe deformity (Fig. 4 ) was significantly higher in the Maasai group than in the Korean group (95 % vs. 0 %), which is in agreement with results from a previous study [ 4 ]. In that previous study, claw toe deformity occurred in 98.79 % of 1096 Maasai people, with the fifth (62.34 %) being the most frequently affected toe.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the prevalence of claw toe deformity (Fig. 4 ) was significantly higher in the Maasai group than in the Korean group (95 % vs. 0 %), which is in agreement with results from a previous study [ 4 ]. In that previous study, claw toe deformity occurred in 98.79 % of 1096 Maasai people, with the fifth (62.34 %) being the most frequently affected toe.…”
Section: Discussionsupporting
confidence: 92%
“…Although they walk long distances (up to 60 km) daily, they do not generally experience foot ailments such as frequent sprain, persistent pain, and osteoarthritis of the midfoot and ankle joint. Our previous study reported the salient features of the feet of 1096 Maasai people grouped by age and sex [ 4 ]. We found that 5.84 and 1.92 % of Maasai participants had bilateral and unilateral fallen medial longitudinal arches (<1 cm), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The Maasai are semi-nomadic pastoralists who walk distances of up to 60 km daily without suffering foot ailments [22]. Walking activity is significant through the mid-50s and accounts for high energy expenditure and cardiorespiratory fitness [23].…”
Section: Discussionmentioning
confidence: 99%
“…Como era de esperarse, el pie con APLM normal fue el más frecuente en hombres y mujeres como lo reportado por Abolarin et al (2011) y Choi et al, (2014. No obstante, mientras estos autores reportan valores de 86,9 % y 91,69 % respectivamente, en este estudio los porcentajes registrados fueron más bajos en hombres y mujeres.…”
Section: Discussionunclassified